The Use of YouTube as Media in Improving Students Speaking Skill: Students’ Perception - Kusumadewi, Hermariyanti; Puspitorini, Ferawaty (Candradimuka: Journal of Education, 2024)
This research aims to investigate the perception of students’ in using Youtube as an effective media to improve students' English-speaking skills. The study employs a qualitative descriptive approach involving participants from grade XI students of vocational school. The design of the study involves descriptive analysis through questionnaires. The results of this research indicate that the qualitative use of YouTube media enhances students' speaking skills. YouTube provides students with opportunities to observe and practice various English speaking situations with easy access to relevant content.  This research contributes to the understanding of the potential use of YouTube media in the context of English language learning, particularly in developing students' speaking skills. The implications of this research are expected to be adopted by educators as an alternative to enhance the effectiveness of English language learning in this digital era.